Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores - Fontoura, Paulo; Rubal, Marcos; Veiga, Puri (Zootaxa, 2017)
Two new species of Eutardigrada were found in supralittoral lichens, growing on rocky shores at two localities of the Western Atlantic coast of the Iberian Peninsula. Ramazzottius littoreus sp. nov., found in San Cibrao (North of Spain), has the dorsal cuticle sculptured with small tubercles and claws with accessory points similar to R. oberhaeuseri. It can be distinguished from all the other known Ramazzottius species with the same type of cuticular sculpture by the dotted egg shell and the peculiar reticulation visible at the bulbous base of egg processes. Macrobiotus halophilus sp. nov., found in Cascais (Centre of Portugal), belongs to the Macrobiotus hufelandi group. The slightly wrinkled egg shell and egg processes in the shape of inverted chalice with dentate distal disc, identifies it as a member of the Macrobiotus persimilis subgroup. The new dioecious species differs from the six other species of the M. persimilis subgroup by a unique combination of some characters (small and very sparse circular cuticular pores, granulation on legs I–III and dentate lunules on legs IV), by measurements of some structures (claws and buccal apparatus), and by the number, dimension and shape of egg processes.